Resource variation and the structure of British bird communities - Lister, Bradford C. (1980)
Data on the foraging microhabitats of British birds are reanalyzed with the aim of understanding how fluctuations in resource abundance affect niche relationships and community structure. At Marley Wood, overlap in the foraging sites of resident bird species increased during the late spring and summer and decreased during the fall and winter. Among bird species coexisting in the pine forests at Thetford Chase, spatial overlap and spatial niche widths were positively correlated with food abundance over a 4-year period. These results suggest that in variable environments similarity in spatial niches is an inverse function of the intensity of competition for food. As food supplies drop, consumer species must apparently occupy increasingly different foraging areas in order to coexist. In less variable environments, however, resource stability may allow finer partitioning of the available foraging space and greater spatial overlap within a given foraging area. The results of this paper also suggest a reinterpretation of MacArthur's study of resource partitioning among warbler species in the boreal forests of New England. Rather than providing an instance of niche segregation in order to avoid intense competition, MacArthur's warblers may actually represent another example of increased spatial similarity when food resources are abundant and competition is reduced.